Evaluasi Manajemen Penyimpanan Sediaan Vaksin Covid-19 Di Instalasi Farmasi Dinas Kesehatan Daerah Provinsi Sulawesi Utara - Kalalo, Michael R. C.; Sambou, Christel N.; Maarisit, Wilmar; Karauwan, Ferdy A. (FMIPA UKIT, 2023)
Vaccine management is one of the management procedures for drug management in healthcare and is critical throughout the healthcare system. This study aims to evaluate the suitability of storing the Covid-19 vaccine in the Pharmacy Installation of the Regional Health Office of Sulawesi Province. This research method is observation with descriptive method. Data collection is done retrospectively with an observation approach or data collection is done all at once. The data taken by this study was carried out using a check list. The research was conducted at the Pharmacy Installation of the Regional Health Office of North Sulawesi Province. The results of the study showed officers and training 1 indicator was appropriate and 2 indicators were not appropriate with a percentage of 33.33%, storage buildings 5 indicators were appropriate and 3 indicators were not compatible with a percentage of 55.55%, storage facilities 8 indicators were appropriate and 11 indicators not according to the percentage of 72.72%, operational storage of 7 indicators according to and 13 indicators not in accordance with the percentage of 53.84%, storage maintenance of 1 indicator according to and 13 indicators not in accordance with the percentage of 7.69%, Qualification, Calibration and Validation of 0 indicators is appropriate and 3 indicators are not in accordance with a percentage of 100%. The conclusion is that overall the percentage is not up to standard with a percentage of 72.72%.